2011
DOI: 10.1016/j.jvolgeores.2010.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and morphological development of Holocene cinder cones: A field and remote sensing study in the Tolbachik volcanic field, Kamchatka

Abstract: The evolution of landscape over time is a central aspect of geological, paleogeographical and geomorphological studies. Volcanic features like cinder cones offer the opportunity to monitor the processes and development of the landscape. Cinder cones are perhaps the simplest and most common volcanic landforms in the world. Morphological and morphometric study of cinder cones has proven an efficient tool for determining their relative dates, and the erosional processes affecting them. The extensive Kamchatka vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 24 publications
1
23
0
2
Order By: Relevance
“…Similar distributions of eruptive volumes are found in Abu volcanic field in Japan (Kiyosugi et al 2010) and Bakony-Balaton Highland in Hungary (Kereszturi et al 2011). Eruptive volumes are orders of magnitude larger in the volcanic fields located along the Trans-Mexican Volcanic Belt, such as in the Jorullo area or Parícutin (Vespermann et al 2000;Pioli et al 2008;Inbar et al 2011). In the Jorullo area, the same eruptive volume range of ≤0.05 km 3 includes about 10 % of the total volcano population ).…”
Section: Useful Terms With Conditions: Small Eruptions and Monogenetimentioning
confidence: 62%
“…Similar distributions of eruptive volumes are found in Abu volcanic field in Japan (Kiyosugi et al 2010) and Bakony-Balaton Highland in Hungary (Kereszturi et al 2011). Eruptive volumes are orders of magnitude larger in the volcanic fields located along the Trans-Mexican Volcanic Belt, such as in the Jorullo area or Parícutin (Vespermann et al 2000;Pioli et al 2008;Inbar et al 2011). In the Jorullo area, the same eruptive volume range of ≤0.05 km 3 includes about 10 % of the total volcano population ).…”
Section: Useful Terms With Conditions: Small Eruptions and Monogenetimentioning
confidence: 62%
“…Although trends in cone erosion have been linked to relative age (e.g. Porter 1973;Settle 1979;Wood 1980a, b;Hooper and Sheridan 1998;Doniz et al 2008;Inbar et al 2011;Fornaciai et al 2012), recent studies have shown that, especially in cases when cones are dominated by fountain-fed spatter eruptions, cone erosion and cone geometry modification are more commonly related to eruptive history or substrate morphology than to time since eruption (Favalli et al 2009;Németh et al 2011;Kereszturi et al 2012;Kereszturi and Németh 2012a). In this respect, we can only say that the inferred 641 AD cones are young, and likely Holocene in age, but it is not possible to better constrain their age using cone morphometry.…”
Section: Historical Accountsmentioning
confidence: 99%
“…gully density), to assess the relative age of scoria cones. Several studies suggested a measurable decrease over time in the H co /W co ratio and in maximum cone slope (Scott and Trask, 1971;Wood, 1980b;Dohrenwend et al, 1986;Hooper and Sheridan, 1998;Inbar et al, 2011). Some of these also argued for a decrease (Dohrenwend et al, 1986;Hooper and Sheridan, 1998) or increase (Inbar and Risso, 2001) in W cr /W co with cone aging but an extensive previous study found no evidence for such a decrease (Wood, 1980b).…”
Section: "Monogenetic" Cone Morphometry: Critical Review Of Previous mentioning
confidence: 99%